Integration of Islamic Values of the Archipelago, Pancasila, and Panca Waluya in Strengthening Student Character in SMAN 23 Bandung - Muliyanti, Indriana (Proceedings: International Seminar On Educational Studies, 2025)
This study aims to analyze the integration of Islamic values of the Archipelago, Pancasila, and Panca Waluya in strengthening character education for students at SMAN 23 Bandung. Islam of the Archipelago teaches moderation, tolerance, mutual cooperation, and respect for local culture, values that are in line with Pancasila as the foundation of the Indonesian state. Meanwhile, Panca Waluya which in Sundanese tradition is embodied in the values of cageur (healthy), bageur (noble character), bener (honest and fair), pinter (intelligent and wise), and singer (responsive and agile) provides a practical dimension in shaping student character. This study used a qualitative method with a case study approach at SMAN 23 Bandung. Data were collected through observation, interviews with teachers and students, and review of school documents. The results show that the integration of these three values is evident in learning, extracurricular activities, the Pancasila student profile strengthening program, and everyday school culture. Islam Nusantara serves as the religious foundation, Pancasila as the ideological framework, and Panca Waluya as the enforcer of character education practices based on local wisdom. This integration contributes to the formation of students who are religious, nationalistic, polite, healthy, intelligent, honest, and have a strong work ethic. Thus, the values of Islam Nusantara, Pancasila, and Panca Waluya are relevant for strengthening character education in the era of globalization.